How do I simplify the term in red box into the underlined term?

C Caesar95 May 2015 13 0 Imperium Romanum May 10, 2015 #1 How do I simplify the term in red box into the underlined term? Attachments 1111 (2).jpg 89.9 KB Views: 10 Last edited by a moderator: May 10, 2015

skipjack Forum Staff Dec 2006 21,481 2,470 May 10, 2015 #2 By multiplying both sides by \(\displaystyle 6x^{2/3}y^{1/2}\), \(\displaystyle \frac16x^{-2/3}y^{1/2} = \frac{1}{10}x^{1/3}y^{-1/2}\) gives \(\displaystyle y = \frac{6}{10}x = 3x/5\).

By multiplying both sides by \(\displaystyle 6x^{2/3}y^{1/2}\), \(\displaystyle \frac16x^{-2/3}y^{1/2} = \frac{1}{10}x^{1/3}y^{-1/2}\) gives \(\displaystyle y = \frac{6}{10}x = 3x/5\).